Karyotype analysis and interspecific hybridization in three perennial Sesbania species (Leguminosae) - Heering, J.H.; Hanson, Jean (Springer, 1993)
The samatic chromosome number in Sesbania in Sesbania sesban var. nubica, S. goetzei and S. keniensis (Leguminosae; papilionoidae) was found to be 2n=12. These findings were in agreement with earlier reports on S. sesban and S. keniensis. The chronomosome number 2n=12 is a new record for S. goetzei. Similarities in Karyotypes were found in the three species. All species had one pair of long metacentric chromosomes; the second pair of metacentric chromosomes pair in S. sesban and S. keniensis. Interspecific crosses in all possible combinations were carried out, resulting in pod and viable seed formation for the crosses S. sesban X S. goetzei, S. sesban X S. keniensis, S. goetzei X S. sesban and S. goetzei X S. keniensis. The two crosses with S. keniensis as a female parent were unsuccessful. The hybrid plants established normally and produced viable seeds.